A Multi Stage Approach for Urban Building Extraction from Remote Sensing Satellite Images - Pendyala, VSSN Gopala Krishna; Kalluri, Hemantha Kumar; Rao, C.V. (International Journal of Engineering and Technology, 2018)
The most important parameter for urban information system is the building information which is represented by the geographic location of the buildings as well as the area, perimeter, density, inter building distances. This data is integrated with demographic data for various applications. High resolution Remote sensing images are widely used as primary data for automatic extraction of building information. Many researchers have developed different methods for maximizing the detection percentage with minimum errors. This paper analyzes the primary data available for researchers, deriving the secondary information and utilizing it effectively. Case studies by various researchers were analyzed and a methodology has been outlined using their experiences, which is expected to be more efficient and reduced errors.